2002
DOI: 10.1002/job.147
|View full text |Cite
|
Sign up to set email alerts
|

Generational differences: revisiting generational work values for the new millennium

Abstract: SummaryAs we enter the new millennium and face the entrance of another generation of workers into the changing world of work, managers are encouraged to deal with the generational differences that appear to exist among workers. This paper revisits the issue of generational differences and the causes of those differences. Data were obtained from more than 350 individuals across the country who responded to a request to complete a survey. Current generational differences in worker values are analysed and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,108
8
112

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,172 publications
(1,307 citation statements)
references
References 18 publications
35
1,108
8
112
Order By: Relevance
“…In line with this ancedotal information, a series of time lag studies conducted by Smola and Sutton (2002) and Twenge et al (2010) confirmed an increased trend towards freedom-related work values in comparison to their counterparts. Freedom work values include, but are not limited to, independence from supervision, autonomy and balance between life and work.…”
Section: Perceived Availability Of Work-life Balancesupporting
confidence: 66%
“…In line with this ancedotal information, a series of time lag studies conducted by Smola and Sutton (2002) and Twenge et al (2010) confirmed an increased trend towards freedom-related work values in comparison to their counterparts. Freedom work values include, but are not limited to, independence from supervision, autonomy and balance between life and work.…”
Section: Perceived Availability Of Work-life Balancesupporting
confidence: 66%
“…This form of CSR is actually highly represented in our manipulation of CSR in Study 2 which may explain the relatively small effect sizes in this study. In addition, the fact that age-related differences between employees may be partly attributable to differences between birth cohorts (Smola and Sutton 2002) may help us to understand why the interaction between CSR-social and age was not significant. It may be that the increasing economic wealth has led particularly the younger cohort to have increased environmental concerns (see Furrer et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, organizations should readily give positive feedback to this generation regarding the ways in which their work has enhanced the success of the firm (Reisenwitz & Iyer, 2009). Moreover, their level of retention is likely to be strongly positively associated with a work environment that provides job challenges as well as opportunities for taking an active role in the development of their careers and skills (Smola and Sutton, 2002) or otherwise they will choose to leave. Prokopeak (2013) points out that while baby boomers leave their employment on average after seven years and for Generation X this figure is every five, Millennials only remain at their place work for an average of two years (Prokopeak, 2013).…”
Section: Career Advancement Opportunities and Employee Retentionmentioning
confidence: 99%